Chapter 6 “When you win, you are a German, when you lose, you are a foreigner” - Ströhle, Claudius (Taylor & Francis, 2024)
With a focus on migrant narratives, or the storytelling about migration, this volume considers the ways in which migration is and has been shaped by individual and collective experiences of agency, belonging and community.